2009
DOI: 10.1016/j.micres.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic evaluation of slime production by conventional and molecular microbiological techniques

Abstract: Twenty-nine staphylococcal isolates from different clinical samples were tested for slime production: phenotypic characterization was carried out using Christensen test (tube test) and Congo red agar plate test (CRA plate test), while the presence and expression of icaA and icaD genes were evaluated by real-time PCR. In 79.3% of studied strains there was a concordance between slime production and presence of icaA and icaD genes, and between lack of slime production and absence of both or only one of the tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
5
28
0
Order By: Relevance
“…In the present study, an association was found between icaD gene detection and biofilm formation, with 100% of the strains harboring icaD and producing biofilm, which is in agreement with the findings of Liberto et al [19]. There was no difference in the distribution of the icaD gene in high-and low-virulence strains, which is in agreement with the findings of Rohde et al [20].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, an association was found between icaD gene detection and biofilm formation, with 100% of the strains harboring icaD and producing biofilm, which is in agreement with the findings of Liberto et al [19]. There was no difference in the distribution of the icaD gene in high-and low-virulence strains, which is in agreement with the findings of Rohde et al [20].…”
Section: Discussionsupporting
confidence: 93%
“…This enzyme requires the product of icaD (IcaD) for full activity (11). Co-expression of icaA and icaD induces higher enzymatic activity (12). The other genes within the ica gene cluster are icaB (polysaccharide deacetylase), icaC (transporter of PIA) and icaR (the regulator gene).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, A. hydrophila isolated from treated wastewater and bay has presented the important viability under heavy metals effect than fish and sea water strains. Therefore, these findings were confirmed by Liberto et al (2007), these researchers have shown that adhesion, bacterial proliferation and slime production increase antibiotic resistance, since drugs may not be able to reach bacteria kept in rein in biofilm.…”
Section: Interaction Between Antibiotics Heavy Metals Resistance Andmentioning
confidence: 64%
“…For example if the isolate was exposed to twelve antibiotics and was tolerant to six antibiotics, the index for the isolate would be 6/12 or 0.50 (Liberto et al, 2007). MAR index value higher than 0.2 is considered to have originated from high-risk sources of contamination like human, commercial poultry farms, swine and dairy cattle where antibiotics are very often used.…”
Section: Multiple Antibiotic Resistances Among Aeromonas Hydrophilamentioning
confidence: 99%